(untitled) (SAARC Journal of Agriculture, 2014)
Chrysanthemum (Chrysanthemum morifolium Ramil) is an important flower crop, being affected by leaf blight caused by Alternaria alternata (Fries) Keissler, a serious disease affecting the flower yield. The present studies were carried out to derive a management strategy with compost teas. The compost teas Vermicompost (CT-1), Vermicompost + Pseudomonas fluorescens1% (CT-2), Vermicompost + Trichoderma viride1% (CT-3), Dung75% + Paddy Straw25% (CT-4), Dung75% + Paddy Straw25% + Pseudomonas fluorescens1% (CT-5), Dung75% + Paddy Straw25% +Trichoderma viride1% (CT-6), Dung75% + Neem Powder20% + Fish meal5% (CT-7), Dung75% + Neem Powder20% + Fish meal5% + Pseudomonas fluorescens1% (CT-8) and Dung75% + Neem Powder20% + Fish meal5% + Trichoderma viride1% (CT-9) were tested against the mycelia growth and spore germination of pathogen, and against disease under field conditions. Compost teas that were sterilized by filtration were prefixed with S where ever necessary. Compost teas were effective in inhibiting the mycelia growth and spore germination. In single spray treatment the percent disease index varied from 9% (CT-8) to 21.34% (CT-4), in two spray treatments 8.69% (SCT-6) to 13.34% (CT-7) and in 3 sprays treatment 4.67% (CT-6) to 11.2% (SCT-1). Treatments CT-6 (4.67%), SCT-5 (4.75%) SCT-6 (6.45%), SCT-7 (5.85%) was superior to fungicide Iprodione 25% + Carbendazim 25%. The treatment CT-6 was most effective to increase the flower yield. DOI: http://dx.doi.org/10.3329/sja.v12i1.21112 SAARC J. Agri., 12(1): 48-61 (2014)